2021
DOI: 10.1021/jacs.1c03588
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally Driven High-Speed Crystal Actuation and Its Simulation

Abstract: Mechanically responsive crystals have been increasingly explored, mainly based on photoisomerization. However, photoisomerization has some disadvantages for crystal actuation, such as a slow actuation speed, no actuation of thick crystals, and a narrow wavelength range. Here we report photothermally driven fast-bending actuation and simulation of a salicylideneaniline derivative crystal with an o-amino substituent in enol form. Under ultraviolet (UV) light irradiation, these thin (<20 μm) crystals bent but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 73 publications
2
92
1
Order By: Relevance
“…The threshold thickness (33 mm) for crystal actuation through the photothermal effect in this study was slightly higher than the threshold thickness (20 mm) reported in a previous study. 41 The thickness dependence of the bending and straightening time constants of enol-1a crystals is shown in Fig. 7b; the time constants for photothermally induced bending (B0.01 s) were two orders of magnitude smaller (i.e., faster) than the time constants for photoisomerisation-induced bending (B1 s), which is consistent with previous reports.…”
Section: Actuation Switching By Crystal Thicknesssupporting
confidence: 90%
See 3 more Smart Citations
“…The threshold thickness (33 mm) for crystal actuation through the photothermal effect in this study was slightly higher than the threshold thickness (20 mm) reported in a previous study. 41 The thickness dependence of the bending and straightening time constants of enol-1a crystals is shown in Fig. 7b; the time constants for photothermally induced bending (B0.01 s) were two orders of magnitude smaller (i.e., faster) than the time constants for photoisomerisation-induced bending (B1 s), which is consistent with previous reports.…”
Section: Actuation Switching By Crystal Thicknesssupporting
confidence: 90%
“…50 Actuation switching is another requirement for the practical application of photomechanical crystals. Among salicylideneaniline crystals, photoisomerisation actuates thin crystals, whereas the photothermal effect actuates thick crystals; 41,50 the photoisomerisation mechanism can be induced by ultraviolet (UV) light alone, whereas the photothermal effect mechanism can be induced by both UV and visible light. 41 Therefore, we hypothesised that crystal actuation could be switched by changing the crystal thickness or light wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photomechanical materials have the property that their constituent nuclei change position after photon absorption, generating a force and displacement that can be harnessed to perform mechanical work [1][2][3]. This change in atomic coordinates could result from heating (photothermal) [4][5][6], a change in electronic state (photostrictive) [7], or a chemical reaction (photochemical) [8].…”
Section: Introductionmentioning
confidence: 99%